2022
DOI: 10.3389/fvets.2022.805382
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Actinobacillus pleuropneumoniae From Clinical Samples Using Recombinase Polymerase Amplification

Abstract: Actinobacillus pleuropneumoniae (APP) is the causative agent of porcine pleuropneumonia, resulting in high economic impact worldwide. There are currently 19 known serovars of APP, with different ones being predominant in specific geographic regions. Outbreaks of pleuropneumonia, characterized by sudden respiratory difficulties and high mortality, can occur when infected pigs are brought into naïve herds, or by those carrying different serovars. Good biosecurity measures include regular diagnostic testing for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…These studies reported using ONT, 31 LAMP, 41 and RPA ( n = 2). 130 , 147 A rapid, long-read metagenomic sequencing study reported using ONT to detect bacterial and fungal pathogens in human, ventilator-associated pneumonia cases compared to a combined standard of culture and qPCR for pathogen detection. 31 They also compared metagenomic ARG detection to culture-based antimicrobial susceptibility testing and found high consistency between the ARGs detected from gram-negative bacterial pathogens with aminoglycoside and beta-lactam resistance phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies reported using ONT, 31 LAMP, 41 and RPA ( n = 2). 130 , 147 A rapid, long-read metagenomic sequencing study reported using ONT to detect bacterial and fungal pathogens in human, ventilator-associated pneumonia cases compared to a combined standard of culture and qPCR for pathogen detection. 31 They also compared metagenomic ARG detection to culture-based antimicrobial susceptibility testing and found high consistency between the ARGs detected from gram-negative bacterial pathogens with aminoglycoside and beta-lactam resistance phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The only animal ONT study included in our scoping review investigated M. bovis in pooled respiratory samples of cattle. 16 The wide application of isothermal techniques for the direct detection of bacterial respiratory pathogens and ARGs in various human and animal settings could be because of the simplicity of operation, potential for a relatively short TAT, low LOD, and ease of interpretation of outputs (e.g., LAMP), 130,147,173 which make these attractive methods to monitor and control outbreaks in resource-limited settings. 41 We found that laboratory tests described as "rapid" had variable descriptions and inclusion of steps from sample collection to reporting of results.…”
Section: Application Of the Laboratory Tests Of Interest In Animals A...mentioning
confidence: 99%
“…pleuropneumoniae and P. multocida are one of the major contributors to porcine respiratory diseases worldwide. The symptoms of infection can include arthritis, breathing difficulties, and lethargy in young pigs (Jensen et al, 1999;Stringer et al, 2022). The incidence rates of A. pleuropneumoniae infection range from 25% to 48%, with a significant mortality rate, thereby causing significant economic losses in the industrial pig breeding industry (Vangroenweghe and Thas, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A. pleuropneumoniae and P. multocida are one of the major contributors to porcine respiratory diseases worldwide. The symptoms of infection can include arthritis, breathing difficulties, and lethargy in young pigs ( Jensen et al, 1999 ; Stringer et al, 2022 ). The incidence rates of A. pleuropneumoniae infection range from 25% to 48%, with a significant mortality rate, thereby causing significant economic losses in the industrial pig breeding industry ( Vangroenweghe and Thas, 2021 ).…”
Section: Discussionmentioning
confidence: 99%